(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Anaplastic thyroid cancer, also known as anaplastic thyroid carcinoma, is an aggressive form of thyroid cancer characterized by uncontrolled growth of cells in the thyroid gland. This form of cancer usually has a very poor prognosis due to its aggressiveness and resistance to cancer treatment. Anaplastic thyroid cancer cells are very abnormal and usually do not look like the original thyroid cells and are poorly differentiated cells that are not specialized for thyroid function.